Unsaturated soil consolidation theory and laboratory experimental data - Rahardjo, Harianto (2011)
The volume change process of an unsaturated soil was considered as a transient flow problem with water and air flowing simultaneously under an applied stress gradient. laboratory experiments were performed to study the volume change behavior of unsaturated soils. Several compacted kaolin specimens were tested using modified Anteus oedometers and triaxial cells. Theoretical analyses were also made to best-fit the results from laboratory experiments. The fitting was accomplished by approximating the compressibility coefficients and adjusting the coefficients of permeability. The comparisons of the results obtained from the theory and the laboratory yield to a similar behavior of volume changes with respect to time.